Dependence of high-order-harmonic-generation yield on driving-laser ellipticity - Möller, Max; Cheng, Yan; Khan, Sabih D.; Zhao, Baozhen; Zhao, Kun; Chini, Michael; Paulus, Gerhard G.; Chang, Zenghu (My University, 2012)
High-order-harmonic-generation yield is remarkably sensitive to driving laser ellipticity, which is interesting from a fundamental point of view as well as for applications. The most well-known example is the generation of isolated attosecond pulses via polarization gating. We develop an intuitive semiclassical model that makes use of the recently measured initial transverse momentum of tunneling ionization. The model is able to predict the dependence of the high-order-harmonic yield on driving laser ellipticity and is in good agreement with experimental results and predictions from a numerically solved time-dependent Schrödinger equation.